2007
DOI: 10.1017/s0265021507001160
|View full text |Cite
|
Sign up to set email alerts
|

A survey of postoperative epidural and intravenous analgesia in Greece

Abstract: Our study discloses important issues regarding the use of intravenous and epidural analgesia and postoperative patient monitoring in Greek hospitals. Implementation of acute pain services that are satisfying the quality criteria may help to improve patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…This finding is in accordance with the results of a recent survey on postoperative analgesia, reporting that epidural catheters were used in 44.5% of Greek Anesthesia Departments. [ 19 ] Similarly, data from Sweden showed that spinals were chosen for short lasting surgical procedures (up to 1 h), while epidurals and CSEs were preferred when postoperative epidural analgesia was planned. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in accordance with the results of a recent survey on postoperative analgesia, reporting that epidural catheters were used in 44.5% of Greek Anesthesia Departments. [ 19 ] Similarly, data from Sweden showed that spinals were chosen for short lasting surgical procedures (up to 1 h), while epidurals and CSEs were preferred when postoperative epidural analgesia was planned. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, such participation rates are relative common in national surveys with a design similar to ours. [ 8 10 19 ] We also consider that our sample size [anesthesiologists ( n = 345) and surgical procedures ( n = 187,703)] is adequate, taking into account the country population. Furthermore, the participating departments were distributed to all major Greek Health Districts, and thus we consider that the results are representative and can be extrapolated nationally.…”
Section: Discussionmentioning
confidence: 99%
“…D espite significant advances in knowledge and in evidence-based interventions, studies continue to report ineffective pain management for acute postoperative pain (Apfelbaum, Chen, Mehta, & Gan, 2003;Gunningberg & Idvall, 2007;Svensson, Sjöström, & Haljamäe, 2001;Tzavellas et al, 2007;Wang & An, 2001). Standards are being developed across the world to guide patient care interventions, increase provider awareness, and monitor outcomes of pain management (American Pain Society [APS], 1995[APS], , 1999American Society of Anesthesiologists, 1995;Australian and New Zealand College of Anaesthetists, 2005;Berry & Dahl, 2000;National Health and Medical Research Council, 1999) though integrative reports reveal ongoing challenges in changing outcomes (Gordon et al, 2005;Max et al, 1991).…”
mentioning
confidence: 99%
“…Standards are being developed across the world to guide patient care interventions, increase provider awareness, and monitor outcomes of pain management (American Pain Society [APS], 1995[APS], , 1999American Society of Anesthesiologists, 1995;Australian and New Zealand College of Anaesthetists, 2005;Berry & Dahl, 2000;National Health and Medical Research Council, 1999) though integrative reports reveal ongoing challenges in changing outcomes (Gordon et al, 2005;Max et al, 1991). Studies continue to demonstrate few changes during the past decade in the inadequacies of postoperative pain management (Dihle, Helseth, Kongsgaard, Paul, & Miaskowski, 2006;Gunningberg & Idvall, 2007;Lee, Chen, & Ngan Kee, 2003;Tzavellas et al, 2007). Mismanaging postoperative pain has a high price; it can lead to negative physiologic and psychological consequences, delay recovery, and have ethical and economic consequences (Kehlet & Dahl, 2003;Rosenberg & Kehlet, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation